Different Diagnostic Findings in patients with Gross Hematuria on Computed Tomography Urography - Tehreem Ata, Sarah Maryam, Muhammad Zakir, S. Qayyum, S. M. Y. Farooq, M. Fatima, A. Iqbal, S. A. Gilani, M. Shafiq, A. Tariq, H. Khan, Leena, S. Sajjad, A. Batool, A. Sial, M. Z. Ul Abidin (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In urine, the presence of abnormal quantity of RBCs is Hematuria. Computed Tomography Urography ability for assessing urothelium and renal parenchyma within particular examination also provides insight into morphological and functional urinary system which may help the physician in better treatment and management of their patients. Aim: To evaluate different diagnostic findings into patients presenting with gross Hematuria on CTU. Methodology: A descriptive study was conducted at Shalamar Hospital Lahore. Data of 113 participants were designated done suitable sample method. For analysis of data 24 SSPS version was used. Results: Out of total number of 113 patients, comprising Out of total number of 113 patients, 33 (29.2%) were females and 80 (70.8%) were males. Out of 113 patients, 42 (37.2%) pateints had gross haemutria, 40 (35.4%) had macroscopic haemtuira and 31 (27.4%) had no haemturia. 25 (22.1%) patients had nephrolithiasis and 88 (77.9%) had not nephrolithiasis. 20 (17.7%) patients had PUJ calculus and 93 (82.3%) had PUJ calculus. 14 (12.4%) patients had urinary tract masses and 99 (87.6%) patients had not urinary tract masses. Out of 113 patients, 58 (51.3%) patients had no calculus and 10 (8.8%) had calculus at distal pole, 30 (26.5%) had calculus at mid pole and 15 (13.3%) had calculus at proximal pole. Mid ureter is the most frequent site for urolithiasis. 27 (23.9%) patients had prostatic abnormalities and 86 (76.1%) patients had not prostatic abnormalities. Conclusion: This study concluded that the utility of CTU is now widely recognized as well as has grown to be the Imaging of choice to evaluate of asymptomatic Hematuria. In our study gross Hematuria are most common in males. The most common site for cause of Hematuria was ureteric calculi and least common site was nephrolithiasis.